Réinventer la sexualité: Remarques sur les derniers écrits de Michel Foucault - Chevalley, Catherine (Revista de Filosofía, 2002)
In this paper I wish to comment on the way we conceive of sexual life today, in connection with Michel Foucault’s characterization of “Sex” as something that is part of a “device for sexuality”. The paper is divided into three parts. In the first part, I attempt to analyze and criticize some major components of our conceptions of sex, namely (a) our belief that sex is a private matter, (b) the view that erotism succeeds to be a philosophical clue to the Subject-Object predicament (G. Bataille), and (c) the thesis that a new civilization based on Eros might be born (H. Marcuse). In the second part, I focus on Foucault’s position, which has been widely misunderstood. Foucault’s general argument was that the mechanics of power in our contemporary societies required a well organized device for sexual practice, theory, medical care and so on, since power required close control over the private life of individuals and the disciplinary training of bodies. He opposed the (c) thesis, which he called the “repressive hypothesis”. He also opposed the (b) view, substituting a “genealogy of the man of desire” for Bataille’s conception of erotism. Finally he opposed the (a) belief, by bringing in debate the spectacular counter-example of Ancient Greek and Latin conceptions of sexuality, to the understanding of which he devoted the last years of his life. The third part of this paper then develops Foucault’s basic assumption that in our present time, to resist power will be possible only if we become able to constitute ourselves as individuals in a new way. I argue that the enigma of sex in our lives essentially exhibits our political, philosophical and ethical weakness. With respect to politics we are deprived of the “power to act”, since every confrontation between individuals and the City has become delu- sive, thus making the art of Greek tragedy barely impossible. With respect to philosophy, we meet the major challenge of a new characterization of the Subject. With respect to ethics, we face the reality of violence everywhere. Our “private tragedies” demonstrate that we recoil into private life mainly because we feel that we have lost the world.